Decrease of serum hCG on day 4 of single-dose methotrexate regimen is valuable to predict treatment failure in patients with intact tubal ectopic pregnancy - Fırat Ekmez; Murat Ekmez (Northwestern Medical Journal, 2021)
Aim: We aimed to determine the predictivity of decrease in serum hCG value on day 4 of single-dose methotrexate (MTX) regimen for the need for surgery in patients with intact tubal ectopic pregnancy (TEP).